The characteristics and operations of “online pharmacies” investigated in relation to medicines popularised during the coronavirus pandemic: a cross-sectional study - Oriakhi, Oria Jason; Almomani, Hamzeh; Patel, Nilesh; Donyai, Parastou (Frontiers in Pharmacology, 2024)
Aim: To explore the characteristics and operations of online pharmacies in relation to medications that gained widespread popularity and increased demand during the COVID-19 pandemic. Furthermore, to assess and compare practices between legitimate and “rogue” online pharmacies. Methods: Fifteen COVID-19-pandemic-related medications were investigated through a UK-based online search. We systematically assessed the credibility of 116 retrieved online pharmacies using the factors: operational location, range of medicines sold, prescription requirements for Prescription Only Medicines (POMs), information exchange, payment/delivery, user-friendliness, legitimacy. Descriptive analysis was conducted, and legitimacy status (legitimate vs. illegitimate/rogue) was tested against relevant safety indicators using a chi-square test. Results: Out of 116 “online pharmacies,” 55 (47%) were confirmed as “rogue,” 47 (41%) were verified as legitimate by the General Pharmaceutical Council (GPhC), and 14 (12%) were verified by other bodies but not by the GPhC. A total of 93 declared their “apparent” physical location of operation on the webpage of which 63 (67.7%, n = 93) declared a location that did not match their actual location according to the online pharmacy’s server (through their IP address). All 15 medicines analysed were readily available for purchase. A high percentage of online pharmacies offered POMs to the public (93.1%, n = 116). Only 23 out of the 116 online pharmacies assessed required a prescription for providing POMs, with only four of these verified as legitimate by the GPhC register, while most of the legitimate pharmacies (44 out of 47) offered online consultations as an alternative option instead of a prescription. Controlled medicines were offered by 28 online pharmacies 27 of which were deemed as rogue. Rogue online pharmacies were significantly more likely to guarantee refunds for medication, not require prescriptions for POMs, and not require an online consultation to obtain POMs. Discussion: Findings reveal easy access to rogue online pharmacies, posing patient safety risks. We also found legitimate online pharmacies often offer online consultations without requiring prescriptions for POMs, raising concerns about inadequate safety checks. This emphasises the need for improved regulations for both types of online pharmacies, especially during public health crises.